Construction Management in the Amazon: Analysis of Performance Indicators and Impacts of COVID-19 - Lopes, Henrique; Lordsleem Jr., Alberto Casado (National Journal of City Management, 2024)
Management failures in public construction projects result in significant resource wastage and delays in social development goals. This research aims to evaluate the management of contracts for public school construction projects using cost, schedule, and scope performance indicators, as well as investigate the influence of the characteristics of the Amazon region and the COVID-19 pandemic on project execution. The methodology involved document analysis of selected samples, describing the projects, geographical locations, contractual changes, and statistical correlation tests. Subsequently, the study surveyed the consequences of the COVID-19 pandemic on the analyzed projects, along with an analysis of performance indicators. The results revealed that all projects experienced cost increases, with an average percentage of 24.36%. Regarding schedule extensions, 92.30% of the projects underwent contractual changes, with an average increase in time of 142.19%. Scope changes were present in all projects, with an average modification percentage of 61.84%. It is believed that this study contributes to a critical analysis of the management of public engineering projects, enabling the identification of problems and improvement opportunities.